2007
DOI: 10.14238/pi47.2.2007.74-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting mortality of neonatal sepsis in Moewardi Hospital, Surakarta

Abstract: N eonatal sepsis is still a significant prob lem found both in developing and de veloped countries. Even though there has been advance in therapy, the morbidity and the mortality are still high. The total of sepsis cases in developing countries is 1.8-18/1000 of birth ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
1
1
0
1
Order By: Relevance
“…In our study, the gestational age variable had p<0.250, then multivariate analysis was carried out using logistic regression but no significant differences were found. This is in line with research conducted at RSUD Dr. Moewardi previously by Hafidh et al (2007) where no significant differences were found in gender and culture growth (Hafidh, 2007). In Rasyida et al (2023) research, significant differences were found where gram-negative bacteria were a predictor of mortality and had an OR of 4.821 (95% CI= 10.18 to 22.842) (Rasyida et al, 2023).…”
Section: Discussionsupporting
confidence: 81%
“…In our study, the gestational age variable had p<0.250, then multivariate analysis was carried out using logistic regression but no significant differences were found. This is in line with research conducted at RSUD Dr. Moewardi previously by Hafidh et al (2007) where no significant differences were found in gender and culture growth (Hafidh, 2007). In Rasyida et al (2023) research, significant differences were found where gram-negative bacteria were a predictor of mortality and had an OR of 4.821 (95% CI= 10.18 to 22.842) (Rasyida et al, 2023).…”
Section: Discussionsupporting
confidence: 81%
“…The association of prematurity with mortality in neonatal sepsis may be due to deficiencies in humoral and cellular immunity. Premature infants have extremely low immunoglobulin levels (except for IgG) to specific maternal antigens, since those immunoglobulins are passively transferred across the placenta in the last trimester of pregnancy [ 14 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…8 Hasil serupa dilaporkan di Rumah Sakit Moewardi Surakarta yang menemukan bahwa angka kematian sepsis neonatus 40%. 18 Perbedaan dalam tingkat kematian pada sepsis neonatus antar negara dapat dijelaskan oleh berbagai faktor, antara lain faktor ekonomi, geografis dan sosial rasial, penggunaan ventilator, inkubator, dan mikroorganisme yang berbeda serta penggunaan antibiotik yang berbeda. 2,4,5 Dalam penelitian kami, sebagian besar kasus kematian disebabkan karena neonatus yang memiliki indikasi perawatan UPIN tidak dapat dirawat, karena kapasitas yang terbatas.…”
Section: Pembahaanunclassified